Filter disc assay of aflatoxin using Bacillus Megaterium and B. Thuringiensis - Tuason, Melissa Marie S.; Dalmacio, Ida F. (1988)
The filter disc plate method of antibiotic assay was tested for the assay of aflatoxin using Bacillus megaterium and B. thuringiensis spores. Significants inhibitions were obtained on the growth of both tests organisms with positive linear correlation between aflatoxin concentration and zones of inhibition. The responses of the test organisms to aflatoxin were not significantly different.